Utilization of the SI APIK Application for Songket Craftsmen in Muara Penimbung Ulu Village - Patmawati, Patmawati; Daud, Rochmawati; Meutia, Inten; rahmawati, meita; khamisah, nur (Faculty of Economics, Universitas Sriwijaya, 2023)
Si Apik is a financial information recording application that can make it easier for micro small businesses to book and record every financial transaction intended for individual / micro businesses or small-scale businesses. This application is an application issued by Bank Indonesia which can be downloaded through the Google Play Store. This application can also be accessed offline which can make it easier for micro small businesses in areas with unstable internet connections to still be able to use this application without problems. This service activity regarding the use of the SI APIK Application is needed by small micro businesses in Muara Penimbung Ulu Village, especially songket craftsmen. Based on the results of the service that has been carried out, it was found that there was an increase in the understanding of songket craftsmen regarding the use of the Si Apik application by 70% from the previous level of understanding of songket craftsmen only by 5.25%.